2013
DOI: 10.1002/app.39821
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic properties and structure of poly(acrylonitrile‐co‐methacrylic acid) polymer solutions for gel spinning at long aging times

Abstract: The objective of the research is to obtain a more complete understanding of how aging affects the viscoelastic properties of polymer solutions to be used as starting materials for gel spinning of polymer fibers. Specifically, poly(acrylonitrile‐co‐methacrylic acid) solutions were prepared and characterized using rheological measurements and nuclear magnetic resonance spectroscopy. The results indicate that elastic character increased with increasing polymer concentration and that gelation of these solutions co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Aging polymer solutions is a well-known procedure to induce aggregation/cluster/ordered structure formation [439][440][441] Fig. 11 and thus to eventually change the viscosity of solutions.…”
Section: Aging Of Polymer Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aging polymer solutions is a well-known procedure to induce aggregation/cluster/ordered structure formation [439][440][441] Fig. 11 and thus to eventually change the viscosity of solutions.…”
Section: Aging Of Polymer Solutionsmentioning
confidence: 99%
“…Aging polymer solutions is a well-known procedure to induce aggregation/cluster/ordered structure formation 439–441 and thus to eventually change the viscosity of solutions. 439,440,442,443 For example, it was shown that the viscoelastic properties of amphiphilic polymer-polyacid supramolecular solutions increased significantly with aging over a period of 30 days until a strong gel was formed, demonstrating the aging time is an important parameter that has to be considered when developing supramolecular systems via the electrostatic interaction between the amphiphilic polycations and polyacid.…”
Section: Efficient Techniques Used To Structure Polymer Chains In Sol...mentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporation of CNTs in PAN microfibers has the potential to improve the physical, mechanical, electrical, and thermal properties of PAN fibers. This can be achieved without any significant weight change and or need to use different production equipment (Brown et al, 2014;Sahin et al, 2014;Li et al, 2018;Mirbaha et al, 2019). These fibers have the potential to be used as a carbon fiber precursor (Mikolajczyk et al, 2010;Sahin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%